2021
DOI: 10.3390/ijms22094751
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Inhibition of miR-130 Family Suppresses Bladder Tumor Growth by Targeting Various Oncogenic Pathways via PTPN1

Abstract: Previously, we have revealed that the miR-130 family (miR-130b, miR-301a, and miR-301b) functions as an oncomiR in bladder cancer. The pharmacological inhibition of the miR-130 family molecules by the seed-targeting strategy with an 8-mer tiny locked nucleic acid (LNA) inhibits the growth, migration, and invasion of bladder cancer cells by repressing stress fiber formation. Here, we searched for a functionally advanced target sequence with LNA for the miR-130 family with low cytotoxicity and found LNA #9 (A(L)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…In lung adenocarcinoma, PTPN1 inhibited cell growth and metastasis through the dephosphorylation of c-Met and PIK3R2 [52] . The latest research on bladder cancer by Monoe et al [53] revealed that PTPN1 knockdown resulted in the increase of cancer cell proliferation and migration, and miR-130-targeted LNA (locked nucleic acid) increased PTPN1 and exhibited as a promising therapeutic agent. However, PTPN1 was also found to be positively correlated with the progression of melanoma [54] and glioma [55] .…”
Section: Discussionmentioning
confidence: 99%
“…In lung adenocarcinoma, PTPN1 inhibited cell growth and metastasis through the dephosphorylation of c-Met and PIK3R2 [52] . The latest research on bladder cancer by Monoe et al [53] revealed that PTPN1 knockdown resulted in the increase of cancer cell proliferation and migration, and miR-130-targeted LNA (locked nucleic acid) increased PTPN1 and exhibited as a promising therapeutic agent. However, PTPN1 was also found to be positively correlated with the progression of melanoma [54] and glioma [55] .…”
Section: Discussionmentioning
confidence: 99%
“…In clear cell renal cell carcinoma, PTPN3 and PTPN13 act as tumor suppressors by inactivating the AKT signaling pathway ( 124 , 125 ), whereas PTPN12 restrains the proliferation of renal cell carcinoma by inhibiting PI3K/mechanistic target of rapamycin (mTOR) pathway activity ( 126 ). In bladder cancer, PTPN1 and PTPN12 function as tumor suppressors to attenuate the growth, invasion and migration of cancer cells ( 127 , 128 ). However, PTPN23 can regulate the motility of bladder cancer cells ( 129 ).…”
Section: Role Of Ptpns In the Context Of Cancermentioning
confidence: 99%
“…By regulating PTPN1, the miRNAs described above serve as tumor suppressors in cancers. Conversely, by targeting PTPN1, a tumor suppressor in bladder cancer, the miR-130 family (miR-130b, miR-301a, and miR-301b) contributes to cancer development ( 127 ).…”
Section: Non-coding Rnas Regulate the Role Of Ptpns In Cancersmentioning
confidence: 99%
“…CD44-associated miRNAs include miR-9, miR-21, miR-34a, miR-130, miR-143, miR-199, and miR-203 [ 22 ]–[ 24 ]. miRNAs are broadly classified into oncogenic (oncomiR) and tumor-suppressive (Anti-oncomiR) miRNAs.…”
Section: Introductionmentioning
confidence: 99%